Protestantska knjižna tradicija in normiranje slovenskega (govorjenega) jezika - Tivadar, Hotimir (Slavia Centralis, 2020)
Protestant Literary Tradition and Standardization of Slovenian (Spoken) LanguageThe Protestant literary tradition, which in Slovenia represents the “living” foundation of the literary language, created the Slovene spoken standard language as a natural construct, which now lives through new technologies and the media (mainly radio and television). In the article, we re-define the attitude towards the role of the literary language and the entire Protestant tradition, but at the same time present the necessity of connecting the written language with the standardization of the modern spoken language. Above all, we emphasize the development of Slovene literary language itself, which is not completely comparable with the close Czech language – in the past, Czech linguistics had (too) much of an influence on Slovenian linguistics.
Keywords: Protestantism; literary language; spoken language; norm; theory of the standard language